SPE/IADC Drilling Conference 1997
DOI: 10.2118/37626-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drillpipe Rotation on Hole Cleaning During Directional Well Drilling

Abstract: The effect of drillpipe rotation on hole cleaning during directional well drilling is investigated. An 8" diameter wellbore simulator, 100 ft long, with a 4 1/2" drillpipe was used for the study. The variables considered in this experimental work are: rotary speed, hole inclination, mud rheology, cuttings size, and mud flow rate. Over 600 tests were conducted. The rotary speed was varied from 0 to 175 rpm. High viscosity and low viscosity bentonite muds and polymer muds were used with 1/4" cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 0 publications
0
29
0
3
Order By: Relevance
“…A number of studies (Sifferman and Becker 1992;Bassal 1996;Brown 1986;Sanchez & Azar 1999) found that the rotation of drillpipe can substantially improve cuttings transport in deviated and horizontals wells. The rotation produces agitation that can resuspend the cuttings, which are deposited on the low-side of a borehole and thus improve hole cleaning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies (Sifferman and Becker 1992;Bassal 1996;Brown 1986;Sanchez & Azar 1999) found that the rotation of drillpipe can substantially improve cuttings transport in deviated and horizontals wells. The rotation produces agitation that can resuspend the cuttings, which are deposited on the low-side of a borehole and thus improve hole cleaning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is recommended to rotate the drillstring even while drilling with a downhole motor (Cameron et al 2003). However, some studies Sanchez & Azar 1999) indicate that drillpipe rotation has a limited effect on hole cleaning when the borehole diameter ratio (D p /D h ) is low or flow rate is high. High rotation speed is usually required to achieve the desired level of hole cleaning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drilling with rotary steerable directional tools also improves drilling efficiency by increasing the percentage of time on bottom by reducing survey time, and time spent correcting for reactive torque. The improvement in hole cleaning due to constantly rotating pipe (12,13) may also reduce or eliminate wiper trips and back reaming.…”
Section: Rotary Steerable Directional Toolsmentioning
confidence: 99%
“…Once again, better results are obtained with a Herschel-Bulkley rheological model. Iyoho and Takahashi [16] present a model on the movement of cutting beds. The movement of the cuttings beds subjected to triangular waves is studied.…”
Section: Analytical Modelsmentioning
confidence: 99%